Exploring the Drivers of Turnover Intentions Among Kindergarten Teachers in Leshan, Sichuan, China - Yu, Xiang (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examines the factors influencing the turnover intentions of kindergarten teachers in Leshan, Sichuan Province, China. It aims to identify key predictors and significant differences among relevant variables. Research design, data and methodology: A quantitative approach was employed, using a questionnaire survey for data collection. The instrument’s validity and reliability were assessed through the Item-Objective Congruence (IOC) index and a pilot test using Cronbach’s Alpha. A total of 300 valid responses were analyzed using Multiple Linear Regression (MLR) to examine significant relationships. Additionally, 40 kindergarten teachers participated in a 14-week strategic intervention, and data collected before and after the intervention were compared using a paired-sample t-test. Results: The MLR analysis indicated that Emotional Workload (EW) and Teacher Job Satisfaction (TJS) were the strongest predictors of kindergarten teachers’ turnover intentions (TTI). Workload (W), Diversity Climate (DC), and Principal Support (PS) also showed significant effects. The paired-sample t-test revealed significant differences in turnover intentions before and after the strategic intervention. Conclusions: The findings underscore the importance of implementing targeted strategies to reduce turnover intentions. Enhancing principal support, improving job satisfaction, reducing both workload and emotional workload, fostering an inclusive environment, and strengthening social support are key recommendations.